Adoptive T cell therapy: An overview of obstacles and opportunities. (1st June 2017) - Baruch, Erez Nissim; Berg, Amy Lauren; Besser, Michal Judith; Schachter, Jacob; Markel, Gal
Abstract : The therapeutic potential of adoptive cell therapy (ACT) in cancer patients was first acknowledged 3 decades ago, but it was an esoteric approach at the time. In recent years, technological advancements have transformed ACT into a viable therapeutic option that can be curative in some patients. In fact, current ACT response rates are 80% to 90% for hematological malignancies and 30% for metastatic melanoma refractory to multiple lines of therapy. Although these results are encouraging, there is still much to be done to fulfill ACT's potential, specifically with regard to improving clinical efficacy, expanding clinical indications, reducing toxicity, and increasing production and cost‐effectiveness. This review addresses the current major obstacles to ACT and presents potential solutions. Cancer 2017;123:2154‐62. © 2017 American Cancer Society . Abstract : Technological advancements have transformed adoptive T cell therapy into a viable therapeutic option that can be curative in some patients. This article reviews the current challenges in this therapeutic modality for cancer as well as possible solutions.